2021
DOI: 10.1097/scs.0000000000008281
|View full text |Cite
|
Sign up to set email alerts
|

Dermoid Cyst of Nasal Tip and Nasal Septum

Abstract: : Dermoid cyst is a congenital and benign disease with most occur on the head and neck. It is rarely that occur on the nasal tip and nasal septum at same time and rarely repair of using nasal septum mucosa. The authors treated a child with dermoid cyst in the nasal tip and septum. Only the dermoid cyst at the tip of the nose caused the change of appearance. Dermoid cyst of nasal septum did not cause any clinical symptoms. She underwent excision of the dermoid cyst at the tip of the nose and endoscopic surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Overall, the prognosis for these lesions was good when complete surgical resection was achieved. Many authors reported no recurrence in their series, and the patients recovered very well [10,15,31].…”
Section: Discussionmentioning
confidence: 88%
“…Overall, the prognosis for these lesions was good when complete surgical resection was achieved. Many authors reported no recurrence in their series, and the patients recovered very well [10,15,31].…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the local mucosa was unimpeded without recurrence. However, an extended period of follow-up is required [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dermoid cysts are uncommon congenital formations that can occur in diverse regions of the human body such as the head, neck, retroperitoneum, ovaries, and brain [5][6][7][8][9]. These cysts commonly present in the head and neck region; most of which, however, are diagnosed before the age of five years old [5].…”
Section: Discussionmentioning
confidence: 99%